A method for preparing a gas-solid separation ceramic membrane based on a phase inversion method and a spraying method

CN117504619BActive Publication Date: 2026-10-30NANJING TECH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311800514.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2026-10-30
Estimated Expiration
2043-12-26

AI Technical Summary

Technical Problem

[0004]上述方法虽然显著提高了陶瓷膜的气通量,但对于小粉尘颗粒分离效率较差,仍未有效解决膜分离领域的“Trade-off”效应,即在一般情况下,减小陶瓷膜的平均孔径可以提高其分离精度,但会增加传质阻力,导致其气通量降低,增大陶瓷膜的平均孔径能够显著提高其气通量,但是会降低其分离精度和对细小颗粒的截留率

Benefits of technology

[0017]气体渗透性和分离精度之间此消彼长的“trade-off”效应是气固分离膜领域亟需解决的问题,本发明提供了一种基于相转化法与喷涂法制备气固分离陶瓷膜的方法,制备出新型双层不对称结构陶瓷膜,显著抑制了“trade-off”效应。该方法具有工艺流程简便、制备周期短,制备成本低等优点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117504619B_ABST
    Figure CN117504619B_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing a gas-solid separation ceramic membrane based on a phase inversion method and a spraying method. Ceramic powder, a polymer, a non-solvent additive, a surfactant, a sintering aid and a polar solvent are mixed and stirred, and then ball-milled to obtain a membrane preparation liquid. After phase inversion, a ceramic green body is obtained, and calcination is performed to obtain a ceramic membrane support. Two kinds of suspensions with different formulations are sprayed on the support, and calcination is performed to obtain a novel double-layer asymmetric structure ceramic membrane. The process is simple, the preparation period is short, the preparation cost is reduced, and industrial large-scale production is realized. By controlling the types and adding amounts of the components in the formulations, the porosity, pore size and distribution degree of the ceramic membrane can be adjusted, the optimization design and precise construction of the pore structure are realized, the 'trade-off' effect between the gas permeability and separation precision which needs to be solved in the membrane field is inhibited, and the preparation of the ceramic membrane with high gas flux, high separation precision and high separation performance for the gas-solid separation field is provided with reference.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing gas-solid separation ceramic membranes based on phase transformation and spraying methods, belonging to the field of ceramic membrane material preparation. Background Technology

[0002] Common gas-solid separation methods include baghouse dust collection, electrostatic precipitators, porous metal dust collectors, cyclone dust collectors, and wet scrubbers. These methods are effective for separating large-particle-size powders, but their efficiency is low for separating micron- and submicron-sized ultrafine powders. Membrane technology, as a novel and efficient separation technology, has advantages such as high interception efficiency, simple operation, and low energy consumption, and holds great potential in the field of high-temperature gas-solid separation. Among them, inorganic gas-solid separation ceramic membranes have become a research hotspot in recent years due to their advantages such as corrosion resistance, thermal shock resistance, high mechanical strength, and high filtration efficiency.

[0003] Inorganic ceramic membranes are generally prepared using a multilayer sintering method, consisting of a separation layer, a transition layer, and a support layer. The pressure difference across the membrane creates a driving force, causing dust-laden gas to pass through the membrane layer, where solid particles are captured and collected by the separation layer, thus achieving gas-solid separation. Gas flux is an important parameter for evaluating the gas-solid separation performance of ceramic membranes. Researchers often increase the gas flux by increasing the pore size and porosity of the ceramic membrane. Cuo et al. [Ceramics International, 2018, 44(10): 11778-11782] prepared porous fiber mullite ceramic dust collector membranes with different fiber contents using a molding method. The porosity was higher than 73%, and the rejection rate for dust particles of 3-10 μm was almost 100%, the rejection rate for 1.0 µm dust particles was 97%, the rejection rate for 0.5 µm dust particles was 87%, and the rejection rate for 0.3 µm dust particles was 82%. Wang et al. [Ceramics International, 2018, 45(6): 6723-6729] prepared a silica / mullite fiber composite membrane with a double-layer structure using a vacuum filtration process. By controlling the mass ratio of silica sol to mullite fiber, the prepared composite membrane had a porosity higher than 90%, with a retention rate of 99% for 1-10 µm particles, 97% for 0.5 µm particles, and 90% for 0.3 µm particles. Zhang et al. [Ceramics International, 2019, 45(9): 11607-11614] prepared a ceramic membrane with an average pore size of 9.85 μm and a gas flux of 820 m³ / h using fused silica and graphite particles as the main raw materials and pore-forming agents. 3 m -2 h -1 kPa -1The rejection rate for 10 μm particles reached 98.6%. Yuan et al. [INDUSTRIAL ENGINEERINGCHEMISTRY RESEARCH, 2020, 59(44): 19680-19688] grew nanostructured CNT films in situ on macroporous SiC supports without introducing a transition layer or sacrificial layer. The average pore size was 14.7 μm, and the gas flux reached 450 m³ / s. 3 m -2 h - 1 kPa -1 The rejection rate for 0.3 μm particles reached 99.48%.

[0004] Although the above methods significantly improve the gas flux of ceramic membranes, they are not very efficient at separating small dust particles and have not effectively solved the "trade-off" effect in the field of membrane separation. That is, under normal circumstances, reducing the average pore size of ceramic membranes can improve their separation accuracy, but it will increase the mass transfer resistance and reduce their gas flux. Increasing the average pore size of ceramic membranes can significantly improve their gas flux, but it will reduce their separation accuracy and the rejection rate of fine particles. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing technologies by proposing a method for preparing high-throughput ceramic membranes based on a phase inversion method combined with a spraying method. This process is simple, efficient, and significantly reduces preparation costs. Furthermore, by controlling the types and amounts of ceramic powder, polymers, non-solvent additives, surfactants, sintering aids, and polar solvents, the porosity, pore size, and distribution of the ceramic membrane can be adjusted, synergistically improving the gas permeability and gas-solid separation accuracy of the ceramic membrane for application in the field of gas-solid separation.

[0006] The technical solution of this invention is as follows: a method for preparing gas-solid separation ceramic membranes based on phase transformation and spraying methods, the specific steps of which are as follows: A. At 30-70 ℃, ceramic powder of a certain particle size, polymer, non-solvent additive, surfactant and sintering aid are added to the polar solvent N-methylpyrrolidone (NMP) in a certain mass ratio, defoamer is added dropwise, and after stirring evenly, the mixture is ball-milled for a period of time to obtain the membrane-forming solution; the sintering aid is one or more of Y2O3, Al2O3, ZrO2, CaO and mullite; the mass ratio of ceramic powder, polymer, non-solvent additive, surfactant, NMP and sintering aid is (20-40):(4-6):1:(0.5-1.5):(30-45):(0.5-1.5); B. The membrane-forming solution is poured onto a clean, smooth glass plate, and coated with a scraper. After coating, it is immediately immersed in pure water for 8-24 minutes. After h, the solidified ceramic green body is separated from the glass plate and dried at 20-80℃ for 4-12 h, followed by calcination to obtain a ceramic support; C. At 30-70 ℃, ceramic powder of a certain particle size, polymer, non-solvent additive, and surfactant are added to the polar solvent N-methylpyrrolidone (NMP) in a certain mass ratio, and defoamer is added dropwise. After stirring evenly, a spray suspension a is obtained; the mass ratio of ceramic powder, polymer, non-solvent additive, surfactant and NMP is (20-40):(4-6):1:(0.5-1.5):(30-45); at 50-100 At ℃, ceramic powder of a certain particle size is added to a solution of 2wt% methylcellulose (MC), defoamer is added dropwise, and after stirring evenly, it is ball-milled for a period of time to obtain spray suspension b; the mass ratio of ceramic powder to methylcellulose (MC) is 1:(2-4); D. Spray suspension a or b is uniformly sprayed onto the surface of the ceramic support prepared in step B through a spray gun. The ceramic support after spraying with spray suspension a is immediately immersed in pure water, and the ceramic support after spraying with spray suspension b is placed in the air. After 8-24 h, it is taken out and dried at 20-80 ℃ for 4-12 h, and then a ceramic film is obtained through a calcination process.

[0007] Preferably, the ceramic powder has a particle size of 0.5-100 μm, and the ceramic powder is one or more of ZrO2, Y2O3, Al2O3, SiO2, SiC, TiO2, Si3N4 or mullite.

[0008] Preferably, the polymer is one of polyethersulfone (PES), polyvinylidene fluoride (PVDF), and polysulfone (PSF).

[0009] Preferably, the non-solvent additive is one of polyethylene glycol (PEG) and polyvinylpyrrolidone (PVP).

[0010] Preferably, the surfactant is one of polysorbate (PS), sodium dodecyl sulfate (SDS), or hexadecyltrimethylammonium bromide (CTAB).

[0011] Preferably, the stirring speed of the film-forming solution is 500-1500 rpm, and the stirring time is 1-4 h.

[0012] The preferred ball milling time is 3-12 h.

[0013] Preferably, the distance between the bottom of the scraper and the substrate during the scraping process is 400-800 μm, and the scraper moving speed is 1-50 mm / s.

[0014] The preferred calcination process involves calcining the green billet at 1100-1800 ℃, controlling the heating and cooling rates at 0.5-3 ℃ / min, and holding the billet for 1-3 h.

[0015] Preferably, the spraying time is 5-15 s and the spraying pressure is 0.1-0.5 MPa.

[0016] The ceramic membranes prepared by this invention have an average pore size of 0.23-5.46 μm, a porosity of 69.02%-84.63%, and a gas permeability of 1042.6-1428.3 μm. 3 m -2 h -1 kPa -1 The filtration efficiency for dust particles with a diameter of less than 0.3 μm is 95.84-99.99%. Beneficial effects

[0017] The trade-off effect between gas permeability and separation accuracy is a pressing problem in the field of gas-solid separation membranes. This invention provides a method for preparing gas-solid separation ceramic membranes based on phase inversion and spraying methods, producing a novel bilayer asymmetric ceramic membrane that significantly suppresses the trade-off effect. This method has advantages such as simple process flow, short preparation cycle, and low preparation cost.

[0018] The microstructure of ceramic membranes prepared by phase inversion combined with spraying is closely related to the type and amount of ceramic powder, polymer, non-solvent additives, surfactants, sintering aids, and polar solvents. Generally, ceramic membranes prepared from smaller particle sizes have smaller average pore sizes. The type of polymer plays a decisive role in the membrane's permeability and physicochemical stability. Polymers solidify in water; increasing the polymer content in the membrane-forming solution can reduce the formation of large pore structures, but it also leads to more pronounced delayed phase separation, resulting in a significantly thickened dense skin layer, reduced porosity, and decreased finger pore connectivity. Adding hydrophilic non-solvent additives such as polyethylene glycol (PEG) and polyvinylpyrrolidone (PVP) to the membrane-forming solution can increase the affinity between the solution and water, providing more water permeability channels and promoting the formation of a thin skin layer and a high-porosity structure. However, excessive amounts of non-solvent additives can increase the viscosity of the membrane-forming solution, inhibiting the rate of water intrusion into the solution, resulting in a denser ceramic membrane structure and reduced gas flux. Surfactants can be classified into cationic surfactants, anionic surfactants, and nonionic surfactants based on their hydrophilic group structure. Adding an appropriate amount of surfactant can reduce the surface tension between the film-forming solution and water, promoting water penetration into the solution and thus increasing the membrane pore size. Polar solvents leach from the solution during film formation and, due to their high solubility in water, act as pore-forming agents, increasing membrane porosity and thus membrane flux. Adding sintering aids can lower the sintering temperature of ceramic membranes and reduce sintering energy consumption.

[0019] By changing the types and amounts of ceramic powder, polymer, non-solvent additives, surfactants, polar solvents, and sintering aids in the membrane-forming solution, the porosity, pore size, and distribution of the ceramic membrane can be adjusted. This allows for precise design of the membrane's internal structure, resulting in an ideal membrane structure and the preparation of ceramic membranes with high porosity, good gas permeability, high separation accuracy, and excellent dust filtration performance. This provides a reference for the preparation of high-throughput ceramic membranes for gas-solid separation.

[0020] This invention discloses a method for preparing gas-solid separation ceramic membranes based on phase transformation and spraying methods. Compared with other ceramic membrane preparation methods, this method is applicable to various types of ceramic materials, has a simple process flow and a short preparation cycle, and can achieve uniform coating of large-area substrates in a short time, greatly reducing preparation costs and enabling large-throughput ceramic membrane materials to be produced and applied on a large scale in the field of gas-solid separation. Attached Figure Description

[0021] Figure 1 This is an electron microscope image of the surface of the ceramic film prepared in Example 2.

[0022] Figure 2 This is an electron microscope image of the cross-section of the ceramic film prepared in Example 2.

[0023] Figure 3 This is an electron microscope image of the surface of the ceramic film prepared in Example 3.

[0024] Figure 4 This is an electron microscope image of the cross-section of the ceramic film prepared in Example 3.

[0025] Figure 5 This is a pore size distribution diagram of the ceramic membrane prepared in Example 3. Detailed Implementation Example 1

[0026] At 30 °C, 15 μm ZrO2 powder, polyethersulfone (PES), polyethylene glycol (PEG), sodium dodecyl sulfate (SDS), Y2O3, and Al2O3 were added to the polar solvent N-methylpyrrolidone (NMP). The mass ratio of ZrO2 powder, PES, PEG, SDS, NMP, Y2O3, and Al2O3 was 20:4:1:0.5:30:0.5. An antifoaming agent was added dropwise, and the mixture was stirred at 500 rpm for 1 h, followed by ball milling for 3 h to obtain the film-forming solution. The film-forming solution was poured onto a clean, smooth glass plate and coated using a doctor blade. The distance between the bottom of the doctor blade and the substrate was 400 μm, and the doctor blade moving speed was 1 mm / s. Immediately after coating, the ceramic green body was immersed in pure water for 8 hours and then separated from the glass plate. It was dried at 20 °C for 4 hours and then heated to 1300 °C at a rate of 0.5 °C / min in air and held for 1 hour to prepare the ceramic support.

[0027] At 30 °C, 0.5 μm ZrO2 powder, polyethersulfone (PES), polyethylene glycol (PEG), and sodium dodecyl sulfate (SDS) were added to the polar solvent N-methylpyrrolidone (NMP), and an antifoaming agent was added dropwise. After stirring at 500 rpm for 1 h, the mixture was ball-milled for 3 h to obtain a spray suspension. The mass ratio of ZrO2 powder, PES, PEG, PS, and NMP was 20:4:1:0.5:30. The spray suspension was uniformly coated onto the surface of a ceramic support using a spray gun. The spraying time was 5 s, and the spraying pressure was 0.1 MPa. Immediately after spraying, the substrate was immersed in pure water for 8 h, then removed and dried at 20 °C for 4 h. Subsequently, the substrate was heated to 1200 °C at a rate of 0.5 °C / min and held at that temperature for 1 h in air to prepare a ceramic membrane. The prepared ceramic membrane had an average pore size of 0.23 μm, a porosity of 74.58%, and a gas permeability of 1042.6 μm. 3 m -2 h -1 kPa -1The filtration efficiency for dust particles with a diameter of less than 0.3 μm is 99.99%. Example 2

[0028] At 40 °C, 20 μm SiC powder, polyethersulfone (PES), polyvinylpyrrolidone (PVP), polysorbate (PS), ZrO2, and mullite were added to the polar solvent N-methylpyrrolidone (NMP). The mass ratio of SiC powder, PES, PVP, PS, NMP, ZrO2, and mullite was 25:5:1:1:40:1. An antifoaming agent was added dropwise, and the mixture was stirred at 800 rpm for 2 h, followed by ball milling for 6 h to obtain the film-forming solution. The film-forming solution was poured onto a clean, smooth glass plate and coated using a doctor blade. The distance between the bottom of the doctor blade and the substrate was 450 μm, and the doctor blade moving speed was 10 mm / s. Immediately after coating, the ceramic green body was immersed in pure water for 12 hours and then separated from the glass plate. It was dried at 40 °C for 8 hours and then heated to 1350 °C at a rate of 1 °C / min in air and held for 2 hours to prepare the ceramic support.

[0029] At 40 °C, 5 μm SiC powder was added to a solution of 2 wt% methylcellulose (MC) at a mass ratio of 1:2. An antifoaming agent was added dropwise, and the mixture was stirred at 800 rpm for 2 h, followed by ball milling for 6 h to obtain a spray suspension. The spray suspension was uniformly coated onto the surface of a ceramic support using a spray gun at a spray time of 10 s and a spray pressure of 0.2 MPa. After spraying, the substrate was placed in air for 12 h, dried at 40 °C for 8 h, and then heated to 1250 °C at a rate of 1 °C / min and held at that temperature for 2 h to prepare a ceramic membrane. The obtained ceramic membrane had an average pore size of 2.13 μm, a porosity of 79.99%, and a gas permeability of 1123.6 μm. 3 m -2 h -1 kPa -1 The filtration efficiency for dust particles with a diameter of less than 0.3 μm is 99.86%.

[0030] Figure 1 This is a SEM image of the ceramic film surface prepared in Example 2. Figure 2 This is a SEM image of the cross-section of the ceramic membrane prepared in Example 2. As can be seen from the image, the prepared ceramic membrane has high porosity, the support layer has a finger-like pore structure, and the separation layer has a particle-stacking structure, forming a bilayer asymmetric structure of the ceramic membrane. Example 3

[0031] At 50 °C, 20 μm SiC powder, polyvinylidene fluoride (PVDF), polyvinylpyrrolidone (PVP), hexadecyltrimethylammonium bromide (CTAB), CaO, and mullite were added to the polar solvent N-methylpyrrolidone (NMP). The mass ratio of SiC powder, PVDF, PVP, CTAB, NMP, CaO, and mullite was 30:6:1:1.5:40:1. An antifoaming agent was added dropwise, and the mixture was stirred at 1200 rpm for 3 h, followed by ball milling for 8 h to obtain the film-forming solution. The film-forming solution was poured onto a clean, smooth glass plate and coated using a doctor blade. The distance between the bottom of the doctor blade and the substrate was 500 μm, and the doctor blade moving speed was 30 mm / s. Immediately after coating, the ceramic green body was immersed in pure water for 16 hours and then separated from the glass plate. It was dried at 60 °C for 10 hours and then heated to 1450 °C at a rate of 2 °C / min in air and held for 2 hours to prepare the ceramic support.

[0032] At 50 °C, 0.5 μm SiC powder, polyvinylidene fluoride (PVDF), polyethylene glycol (PEG), and hexadecyltrimethylammonium bromide (CTAB) were added to the polar solvent N-methylpyrrolidone (NMP), and an antifoaming agent was added dropwise. After stirring at 1200 rpm for 3 h, the mixture was ball-milled for 8 h to obtain a spray suspension. The mass ratio of SiC powder, PVDF, PEG, CTAB, and NMP was 30:6:1:1.5:40. The spray suspension was uniformly coated onto the surface of a ceramic support using a spray gun. The spraying time was 10 s, and the spraying pressure was 0.3 MPa. Immediately after spraying, the substrate was immersed in pure water for 16 h, then removed and dried at 60 °C for 10 h. Subsequently, the substrate was heated to 1250 °C at a rate of 2 °C / min and held at that temperature for 2 h in air to prepare a ceramic membrane. The prepared ceramic membrane had an average pore size of 3.03 μm, a porosity of 84.63%, and a gas permeability of 1428.3 μm. 3 m -2 h -1 kPa -1 The filtration efficiency for dust particles with a diameter of less than 0.3 μm is 99.98%.

[0033] Table 1 compares the properties of the ceramic film prepared by phase transformation method combined with spraying in Example 3 with those in the literature. Figure 3 This is a SEM image of the ceramic film surface prepared in Example 3. Figure 4 This is a SEM image of the cross-section of the ceramic membrane prepared in Example 3. Figure 5This is a pore size distribution diagram of the ceramic membrane prepared in Example 3. As can be seen from the figure, the prepared ceramic membrane has high porosity and concentrated pore size distribution. The support layer has a finger-like pore structure, and the separation layer also has a finger-like pore structure, forming a bilayer asymmetric structure of the ceramic membrane. Example 4

[0034] At 70 °C, 100 μm Al₂O₃ and TiO₂ powders, polysulfone (PSF), polyethylene glycol (PEG), sodium dodecyl sulfate (SDS), Y₂O₃, and CaO were added to the polar solvent N-methylpyrrolidone (NMP). The mass ratio of Al₂O₃ and TiO₂ powders, polyvinylidene fluoride (PVDF), polyvinylpyrrolidone (PVP), hexadecyltrimethylammonium bromide (CTAB), NMP, Y₂O₃, and CaO powders was 40:6:1:1.5:45:1.5. An antifoaming agent was added dropwise, and the mixture was stirred at 1500 rpm for 4 h, followed by ball milling for 12 h to obtain the film-forming solution. The film-forming solution was poured onto a clean, smooth glass plate and coated using a doctor blade. The distance between the bottom of the doctor blade and the substrate was 800 μm, and the doctor blade moving speed was 50 mm / s. Immediately after coating, the ceramic green body was immersed in pure water for 24 hours and then separated from the glass plate. It was dried at 80 °C for 12 hours and then heated to 1800 °C at a rate of 3 °C / min in air and held for 3 hours to prepare the ceramic support.

[0035] At 70 °C, 20 μm SiC powder was added to a solution of 2 wt% methyl cellulose (MC) at a mass ratio of 1:4. An antifoaming agent was added dropwise, and the mixture was stirred at 1500 rpm for 4 h, followed by ball milling for 12 h to obtain a spray suspension. The spray suspension was uniformly coated onto the surface of a ceramic support using a spray gun at a spray time of 15 s and a spray pressure of 0.5 MPa. After spraying, the substrate was placed in air for 24 h, dried at 80 °C for 12 h, and then heated to 1450 °C at a rate of 3 °C / min and held at that temperature for 3 h to prepare a ceramic membrane. The obtained ceramic membrane had an average pore size of 5.46 μm, a porosity of 69.02%, and a gas permeability of 1228.6 μm. 3 m -2 h -1 kPa -1 The filtration efficiency for dust particles with a diameter of less than 0.3 μm is 95.84%.

[0036] Table 1 compares the performance of the ceramic membrane prepared in Example 3 with that in the literature. Wei et al. [J Membr Sci, 2017, 540: 381-390] silicon carbide 2.31 40 105.2 For dust particles with a diameter less than 0.3 μm: 99.95 Cuo et al. [Ceramics International, 2018, 44(10): 11778-11782] Mullite / >73 / For dust particles with a diameter of 3–10 μm: almost 100; for dust particles with a diameter less than 1.0 μm: 97; for dust particles with a diameter less than 0.5 μm: 87; for dust particles with a diameter less than 0.3 μm: 82. Wang et al. [Ceramics International, 2018, 45(6): 6723-6729] Silica / Mullite / >90 / For dust particles with a diameter of 1-10 μm: 99; for dust particles with a diameter less than 0.5 μm: 97; for dust particles with a diameter less than 0.3 μm: 90. Liu et al. [Ceramics International, 2018, 45(3):3921-3929] silicon carbide 9.9 / 194 / Zhang et al. [Ceramics International, 2019, 45(9): 11607-11614] Fused Quartz 9.85 / 820 For dust particles with a diameter less than 10 μm: 98.6 Yuan et al[INDUSTRIALENGINEERING CHEMISTRYRESEARCH,2020,59(44):19680-19688] silicon carbide 14.7 / 450 For dust particles with a diameter less than 0.3 μm: 99.48 Qiao et al. [J Membr Sci, 2020, 594, 117464] silicon carbide 2-5 / 240-277 For dust particles with a diameter less than 0.5 μm: 99.8 Chen et al[ChemicalEngineering Journal,2021,420(P3)] silicon carbide / / 65 For dust particles with a diameter less than 0.3 μm: 99.99 Example 3 silicon carbide 3.03 84.63 1428.3 For dust particles with a diameter less than 0.3 μm: 99.98%

Claims

1. A method for preparing gas-solid separation ceramic membranes based on phase transformation and spraying methods, characterized in that: The specific steps are as follows: A. At 30-70 ℃, ceramic powder of a certain particle size, polymer, non-solvent additive, surfactant and sintering aid are added to the polar solvent N-methylpyrrolidone (NMP) in a certain mass ratio. Defoamer is added dropwise, and after stirring evenly, the mixture is ball-milled for a period of time to obtain the film-forming solution. The sintering aid is one or more of Y2O3, Al2O3, ZrO2, CaO and mullite. The mass ratio of ceramic powder, polymer, non-solvent additive, surfactant, NMP and sintering aid is (20-40):(4-6):1:(0.5-1.5):(30-45):(0.5-1.5). B. Pour the film-forming solution onto a clean, smooth glass plate and apply it using a scraper. Immediately after application, immerse the solidified ceramic green body in pure water for 8-24 hours. Separate the solidified ceramic green body from the glass plate and dry it at 20-80 ℃ for 4-12 hours. Then, calcinate it to obtain the ceramic support. C. At 30-70 ℃, ceramic powder of a certain particle size, polymer, non-solvent additive, and surfactant are added to the polar solvent N-methylpyrrolidone (NMP) in a certain mass ratio, and defoamer is added dropwise. After stirring evenly, a spray suspension a is obtained; the mass ratio of ceramic powder, polymer, non-solvent additive, surfactant, and NMP is (20-40):(4-6):1:(0.5-1.5):(30-45); At 50-100 ℃, ceramic powder of a certain particle size is added to a solution of 2wt% methylcellulose (MC), and defoamer is added dropwise. After stirring evenly, it is ball-milled for a period of time to obtain a spray suspension b; the mass ratio of ceramic powder to methylcellulose (MC) is 1:(2-4). D. Spray suspension a or b evenly onto the surface of the ceramic support prepared in step B using a spray gun. The ceramic support after spraying with suspension a is immediately immersed in pure water, while the ceramic support after spraying with suspension b is placed in air. After 8-24 hours, it is removed and dried at 20-80 ℃ for 4-12 hours, followed by a calcination process to obtain a ceramic film. The spraying time is 5-15 seconds, and the spraying pressure is 0.1-0.5 MPa. The calcination process described in steps B and D involves calcining the green billet at 1100-1800 ℃, controlling the heating and cooling rates at 0.5-3 ℃ / min, and holding the billet for 1-3 h.

2. The method for preparing gas-solid separation ceramic membranes based on phase transformation and spraying methods according to claim 1, characterized in that: The ceramic powder mentioned in steps A and C has a particle size of 0.5-100 μm, and the ceramic powder is one or more of ZrO2, Y2O3, Al2O3, SiO2, SiC, TiO2, Si3N4 or mullite.

3. The method for preparing gas-solid separation ceramic membranes based on phase transformation and spraying methods according to claim 1, characterized in that: The polymer mentioned in steps A and C is one of polyethersulfone (PES), polyvinylidene fluoride (PVDF), and polysulfone (PSF).

4. The method for preparing gas-solid separation ceramic membranes based on phase transformation and spraying methods according to claim 1, characterized in that: The non-solvent additive mentioned in steps A and C is one of polyethylene glycol (PEG) and polyvinylpyrrolidone (PVP).

5. The method for preparing gas-solid separation ceramic membranes based on phase transformation and spraying methods according to claim 1, characterized in that: The surfactant mentioned in steps A and C is one of polysorbate (PS), sodium dodecyl sulfate (SDS), and hexadecyltrimethylammonium bromide (CTAB).

6. The method for preparing gas-solid separation ceramic membranes based on phase transformation and spraying methods according to claim 1, characterized in that: The stirring speed of the film-forming solution in step A, and the spray suspensions a and b in step C are 500-1500 rpm, and the stirring time is 1-4 h.

7. The method for preparing gas-solid separation ceramic membranes based on phase transformation and spraying methods according to claim 1, characterized in that: The ball milling time mentioned in steps A and C is 3-12 hours.

8. The method for preparing gas-solid separation ceramic membranes based on phase transformation and spraying methods according to claim 1, characterized in that: In step B, the distance between the bottom of the squeegee and the substrate during the coating process is 400-800 μm, and the squeegee moving speed is 1-50 mm / s.

Citation Information

Patent Citations

  • Production method of aluminum oxide ceramic membrane of asymmetric porous structure

    CN109865433A

  • Co-sintering preparation method of silicon carbide ceramic support body and film layer

    CN115572178A

  • Method for manufacturing separation membrane and separation membrane

    JP2021023938A